THE GASING METHOD HAS SUCCESSFULLY IMPROVED NUMERATION RATIO IN VARIOUS REGIONS OF INDONESIA - Gusmara, Eriya; Prihantini; Rendi Restiana Sukardi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Numeracy skills have become a highly crucial foundational competence in responding to the demands of the 21st century, particularly in the development of mathematical literacy and problem-solving abilities. However, the numeracy achievement of students in Indonesia remains relatively low, as indicated by reports from PISA and the National Assessment. This study aims to analyze the effectiveness of the Gasing Method (Gampang, Asyik, dan Menyenangkan / Easy, Fun, and Enjoyable) in improving students’ numeracy skills across various regions in Indonesia. The research employed a quantitative approach using a pre-experimental one-group pretest–posttest design. The sample consisted of 203 participants from four regions: Mesuji Regency, Karanganyar Regency, Bojonegoro Regency, and Bandar Lampung City. Data were collected through numeracy test instruments (pretest and posttest) and analyzed using descriptive statistics and a Two-Way ANOVA test with SPSS. The results indicate a significant improvement in numeracy skills across all regions, where the average pretest scores were in the low to moderate categories and subsequently increased sharply to nearly the maximum scores in the posttest. The Two-Way ANOVA analysis confirms that the implementation of the Gasing Method has a significant effect on improving numeracy skills (Sig. < 0.001), with an R² value of 0.688, indicating a strong contribution of the model to the increase in scores. These findings provide empirical evidence that the Gasing Method is effective, adaptable across diverse regional contexts, and relevant as a learning strategy to strengthen numeracy skills in Indonesia.